Two new species of Euphranta Loew (Diptera: Tephritidae: Trypetiane) and an updated key for the species from India - David, K. J.; Singh, Shakti Kumar (Zootaxa, 2015)
Two new species of genus Euphranta Loew, namely E. wrightiae sp. nov. and E. pseudocassiae sp. nov. are described from India. An updated key to Indian species of Euphranta is also provided.